Physico-Chemical Studies of ?-bonded Complexes of Dialkyltin(IV) cations with N-(o-anisyl) and N-(p-anisyl)-2-Mercaptoacetamides - S. Rathour, Gattu; Bhagchandani, Pushpa (Asian Journal of Chemistry, 2010)
In the present work, a comparative study of the stability constants of σ-bonded dialkyltin(IV) cations with N-(o-anisyl) and N-(p-anisyl)-2-mercaptoacetamide have been described.